Bis(permethylpentalene)cerium--another ambiguity in lanthanide oxidation state. - Ashley, A; Balazs, G; Cowley, A; Green, J; Booth, C; O'Hare, D (2007)
Ce(eta(8)-C(8)Me(6))(2) exists in a valency close to Ce(iii) with some Ce(iv) and provides an example of the Kondo effect in a discrete molecule.